The use of Flashcards in teaching EFL vocabulary in online learning - Khan, Raja Muhammad Ishtiaq (Register Journal, 2022)
The outbreak of COVID-19 has altered the way of language instruction. Vocabulary learning is an essential aspect of the language learning and teaching process that needs careful attention and consideration. Teaching vocabulary becomes more critical when learners cannot attend physical classes. The present study explores the impact of flashcards in learning vocabulary in an online context. The study adopted a quasi-experimental design to gather the data. The study was carried on two performed intact groups of intermediate-level learners. A vocabulary test was used to collect the data as pre and posttests. The intervention of the flashcards was continued for seven weeks. All the learners were informed about the process of the research. The result implies that the incorporation of flashcards impacted learners' vocabulary learning during online instruction. The data analysis asserts that flashcards have helped the experimental group to develop their vocabulary. The results indicate that flashcards are beneficial in the virtual learning environment. Keywords: Flashcards, EFL, Online learning, Vocabulary